Bacterial Photosensory Proteins and Their Role in Plant–pathogen Interactions - Kraiselburd, Ivana (2017)
Light is an important environmental signal for almost all living organisms. The light perception is achieved by photoreceptor proteins. As can be observed from the great number of bacterial genomes sequenced, plant pathogenic bacteria encode for a large number of photoreceptor proteins. The physiological implications of these photoreceptors are still poorly characterized. However, recent studies revealed the participation of these photosensory proteins in the pathogenic process. Here, we summarize what is known about these proteins and their role during the virulence process, concluding that the light environment modulates the plant–pathogen interaction.